1998
DOI: 10.1159/000017048
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Differentiation of Frontal Lobe Degeneration of the Non-Alzheimer Type and Alzheimer’s Disease

Abstract: Neuropsychological differences between 14 patients with a clinical diagnosis of frontal lobe degeneration of non-Alzheimer type (FLD) and 15 patients with a clinical diagnosis of Alzheimer’s disease (AD) were studied. The most efficient psychometric predictors of FLD were Digit Symbol, estimation tasks, word list recall, and particularly the FAS word fluency test. Behavioral predictors of FLD and AD showed a double dissociation: regression and impulsivity characterized FLD, whereas lack of motivation and slown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 36 publications
4
39
0
Order By: Relevance
“…While it takes less than 10 min to finish MMSE, SNSB-D requires more than an hour to complete the whole battery, which may well reduce the motivation of patients. Moreover, motivation to perform tests tends to decrease with AD progression due to the gradual deterioration of frontal lobe function [30]. In this way, it may be less effective to track the general cognitive decline in dementia patients with AD using the whole neuropsychological battery (SNSB-D GCF score).…”
Section: Discussionmentioning
confidence: 99%
“…While it takes less than 10 min to finish MMSE, SNSB-D requires more than an hour to complete the whole battery, which may well reduce the motivation of patients. Moreover, motivation to perform tests tends to decrease with AD progression due to the gradual deterioration of frontal lobe function [30]. In this way, it may be less effective to track the general cognitive decline in dementia patients with AD using the whole neuropsychological battery (SNSB-D GCF score).…”
Section: Discussionmentioning
confidence: 99%
“…The profiles of cognitive deficits exhibited by FTD and AD patients on the MDRS parallel those seen with more extensive testing. Several studies have shown greater memory impairment in AD than in FTD for both verbal (Elfgren et al, 1994;Kramer et al, 2003;Lindau et al, 1998;Perry & Hodges, 2000;Rosen et al, 2004;Thomas-Anterion et al, 2000) and visual (Frisoni et al, 1995;Kertesz et al, 2003a;Kramer et al, 2003;Pachana et al, 1996;Perry & Hodges, 2000) materials, a finding that has been attributed to greater medial temporolimbic pathology in AD (Braak & Braak, 1991) than in FTD (Frisoni et al, 1996;Lavenu et al, 1998). Similarly, a larger deficit in conceptual abilities in FTD than in AD has been shown on tests of conceptual processing and verbal abstraction (Kertesz et al, 2003a;Slachevsky et al, 2004).…”
Section: Cognitive Dysfunction In Ftdmentioning
confidence: 99%
“…Accurate differential diagnosis is crucial, however, given potential differences in prognosis (Rascovsky et al, 2005) and in pharmacological management strategies that might be suggested by different neurotransmitter system involvement in the two disorders Moretti et al, 2003;Pasquier et al, 2003;Qume et al, 1994;Rahman et al, 1999;Sparks & Markesbery, 1991;Swartz et al, 1997). Recent studies using batteries of neuropsychological tests suggest that FTD and AD are associated with distinct cognitive profiles that might aid in their differential diagnosis (Binetti et al, 2000;Elfgren et al, 1994;Frisoni et al, 1995;Gregory et al, 1997;Kramer et al, 2003;Lindau et al, 1998;Mendez et al, 1996;Pachana et al, 1996;Rascovsky et al, 2002;Thomas-Anterion et al, 2000). Particularly compelling are retrospective studies that have shown a double dissociation in which mildly-to-moderately demented patients with autopsy-confirmed FTD are more impaired than those with autopsy-confirmed AD on tests sensitive to frontal lobe dysfunction (e.g., word generation tasks), but less impaired on tests of memory and visuospatial abilities sensitive to dysfunction of medial temporal and parietal association cortices (e.g., Rascovsky et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…45 Using discriminant analysis, one study found that the FAS word fluency test was the instrument that best differentiated FTD from AD. 46 Although it has been suggested that tests of constructional ability differ significantly between FTD and AD, 43 this is not always the case. 46 Some patients with AD demonstrate substantial executive deficits; 47 hence neither the clinical nor neuropsychologic profile of the frontotemporal syndrome is specific for FTD.…”
Section: Vascular Dementia (Vad)mentioning
confidence: 99%
“…46 Although it has been suggested that tests of constructional ability differ significantly between FTD and AD, 43 this is not always the case. 46 Some patients with AD demonstrate substantial executive deficits; 47 hence neither the clinical nor neuropsychologic profile of the frontotemporal syndrome is specific for FTD. There are no clinical features that are useful for establishing either the histologic subtype of FTD or linkage to tau mutations.…”
Section: Vascular Dementia (Vad)mentioning
confidence: 99%